Infant Oxygen Supply Automatic Monitoring System - Aziz, Munirah; Abdul Jamil, Muhammad Mahadi (Evolution in Electrical and Electronic Engineering, 2025)
Infants and young children, especially those born prematurely or with breathing problems, often struggle to breathe properly because their lungs are not fully developed. Oxygen therapy is essential to help them survive and grow. However, manually checking their oxygen levels takes time and leads to human errors. These mistakes can cause serious complications like hypoxia (too little oxygen) or oxygen toxicity (too much oxygen), which may affect the child’s long-term health. To reduce the risk, developed the Infant and Child Oxygen Supply Automatic Monitoring System. This system is designed to continuously monitor vital signs such as heart rate, oxygen saturation (SpO2), and temperature in real-time. It is built using the MAX30102 sensor, ESP32 microcontroller, and piezoelectric sensor, which helps provide the right amount of oxygen based on the child’s health condition. The system also includes a mobile app that allows caregivers and patients to view live data and receive alerts if there are any irregularities, so can take quick action even from a distance. This smart system offers better support in neonatal and pediatric care especially in settings where proper oxygen monitoring tools are lacking. It helps reduce the workload for healthcare staff and gives families peace of mind.